Lessons to Demonstrate Statistical Literacy Skills: A Case Study of Japanese High School Students on Reading Statistical Reports - Shunya Koga (Journal of Statistics and Data Science Education)
Statistical literacy, encompassing the interpretation and evaluation of statistical reports, is a skill developed in schools. However, the pedagogical approaches to statistical literacy skills have not been sufficiently investigated. This study investigated whether statistical literacy skills could be demonstrated through high school lessons. These lessons include a statistical literacy process, grounded in critical thinking principles, to facilitate students’ interpretation and evaluation of statistical reports. Additionally, a corresponding worksheet, aligning with this process, is included in the lessons to help students comprehend statistical reports. Seven 50-min lessons were conducted with 34 high school students, aged between 17 and 18 years, using this worksheet. Additionally, a statistical literacy skills test, designed to assess various statistical literacy skills within a short timeframe, was developed and administered at the beginning of the first lesson and at the end of the last lesson. The outcomes revealed that students were able to demonstrate some skills and effectively evaluate statistical reports. This study makes notable contributions by introducing a structured statistical literacy process and an associated skills assessment test. These tools can serve as valuable resources for students seeking to critically evaluate statistical reports and enable educators to gauge the extent of students’ acquisition. Supplementary materials for this article are available online.